Symbiont Acquisition and Replacement as a Source of Ecological Innovation. Issue 5 (May 2017) - Sudakaran, Sailendharan; Kost, Christian; Kaltenpoth, Martin
Abstract : Nutritional symbionts play a major role in the ecology and evolution of insects. The recent accumulation of knowledge on the identity, function, genomics, and phylogenetic relationships of insect–bacteria symbioses provides the opportunity to assess the effects of symbiont acquisitions and replacements on the shift into novel ecological niches and subsequent lineage diversification. The megadiverse insect order Hemiptera presents a particularly large diversity of symbiotic associations that has frequently undergone shifts in symbiont localization and identity, which have contributed to the exploitation of nutritionally imbalanced diets such as plant saps or vertebrate blood. Here we review the known ecological and evolutionary implications of symbiont gains, switches, and replacements, and identify future research directions that can contribute to a more comprehensive understanding of symbiosis as a major driving force of ecological adaptation. Trends: Microbial symbionts can confer beneficial traits on their insect hosts and contribute to the hosts' adaptation to novel ecological niches. In the megadiverse insect order Hemiptera, obligate symbionts have been acquired and replaced many times independently. Symbiont acquisitions and replacements can mitigate the perilous effects of genomic decay in long-term symbioses and/or facilitate the adaptation to new host plants, thus providing the opportunity for niche expansion and diversification. Our current understanding of the ecological implications of symbiont acquisitions and replacements is hampered by a lack of detailed knowledge about the nutritional ecology of closely related insect taxa with different symbionts.